Fenomena Hollow Shell Effect Pada Aplikasi Finansial: Evaluasi Paradoksal User Experience Kaspro di Kalangan Pengemudi Maxim - Ilham Al Hafidz Muhyiddien; Ispandi Ispandi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Digital transformation in the online transportation sector positions digital wallets not merely as optional payment tools, but as absolute work infrastructures for driver partners. This study aims to critically evaluate user satisfaction and experience with the KasPro application within the Maxim Driver Jabodetabek community. Given the high mobility and heterogeneity of the gig worker population, this research is positioned as an exploratory quantitative study. Data collection involved 99 respondents, determined using Slovin's formula with a 10% margin of error through purposive sampling techniques. Evaluation using the User Experience Questionnaire (UEQ) instrument revealed a sharp usability paradox. The Perspicuity scale achieved a highly satisfactory positive score (2.32), indicating an easily learnable interface. However, the other five crucial dimensions fell into the Bad category with extreme negative values: Attractiveness (-2.39), Efficiency (-2.42), Dependability (-2.50), Stimulation (-2.46), and Novelty (-2.35). Theoretically, this anomaly, where Perspicuity is inversely proportional to functional satisfaction, occurs due to the Hollow Shell Effect under conditions of forced adoption. For gig workers who have an absolute dependence on daily income liquidity, visual navigational ease instantly loses its significance when the system fails to meet basic utilities such as access speed and financial transaction security. This gap triggers passive resistance behavior, where users minimize operational interaction. The main contribution of this research is expanding human-computer interaction literature by validating the Hollow Shell Effect anomaly within the gig worker ecosystem, and proposing a design paradigm shift towards Reliability-First UX principles. Therefore, developers are recommended to prioritize backend infrastructure optimization through microservices architecture and e-KYC system automation, rather than simply carrying out visual aesthetic updates.